Pengaruh Tren Joget Tiktok Terhadap Karakteristik Siswa SD - Yusro, Achmad Fajar; Desiningrum, Noviana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid development of social media has significantly influenced children's behavior, including elementary school (SD) students. One of the trending activities is the TikTok dance challenge, which involves creating and sharing dance videos through the TikTok platform. This research aims to examine the impact of the TikTok dance trend on the characteristics of elementary school students. This article is a literature review that seeks to analyze how the TikTok dance trend affects the characteristics of elementary school students from social, emotional, and academic aspects. This study employs a qualitative approach using literature review methods. Data collection techniques were carried out through relevant scientific sources in databases on Google Scholar. Data analysis techniques were conducted qualitatively with stages of data reduction, data presentation, and drawing conclusions. The study results show that this trend has a dual impact, on one hand supporting children's self-expression and creativity, but on the other hand causing challenges such as learning distractions and the negative influence of adult content. Therefore, the role of guidance from parents and teachers becomes the key factor in minimizing the negative effects of this trend.